Miss Winter in the library with a knife - Edwards, Martin, 1955- (Poisoned Pen Press, 2025)
"YOU ARE CORDIALLY INVITED to an all-expenses-paid Christmas holiday at Midwinter, a remote hamlet in the North Pennines in Yorkshire, England, to play a murder mystery game. Joining you are a has-been mystery author infamous for copycatting the classics, an out of work publicist, a disgraced influencer whose off-the-record remarks have come back to bite her, a true crime podcaster who's been sued for every penny, a former hotshot literary agent who's been sued for sexual harassment, and a publisher who used AI to plagiarize bestsellers--and was sued by Netflix. Oddly, the contestants also share a lack of any next-of-kin who might notice or care if they disappear. But no matter! There are cash prizes for all who see the game through to the end, and of course a high-stakes Grand Prize for the winner that no one is allowed to discuss. But it's promised to be life-altering. And then one by one, people start dying.."-- Provided by publisher.